THE EXISTENCE OF THE BAOLEK TRADITION: A STUDY OF TRADITIONAL WEDDINGS IN PARIT BARU VILLAGE THROUGH THE LENS OF ISLAMIC FAMILY LAW - Salim, Muhammad Abdullah; Yustiloviani, Yustiloviani; Alfiander, Dodon (UIN Mahmud Yunus Batusangkar, 2024)
This research explores the existence of the Baolek tradition in traditional weddings in Parit Baru Village, where this custom is considered mandatory. Couples who do not perform this tradition, often due to financial constraints, are not allowed to live together until the tradition is fulfilled. The study aims to uncover the background and ceremonial processes of the Baolek tradition, its significance, and its implications for the community.The findings reveal that the Baolek tradition serves to publicly announce a marriage and prevent potential social conflicts or slander within the community. It is a deeply ingrained practice in Parit Baru Village, where newlyweds are required to carry out Baolek as a social obligation. If financial limitations hinder the couple from performing the tradition, they are required to live separately (known as Bausah) for a period ranging from one week to one month, while preparing the necessary resources.Regardless of the scale, the Baolek tradition involves significant financial contributions, as it is customary to entertain the entire community. To support the couple, the nuclear family, including Ninik Mamak (elders), typically provides assistance to ensure the tradition can proceed, even in a modest form. Failure to perform the Baolek tradition results in social sanctions, including ostracization, exclusion from customary practices, and strained familial relationships.In conclusion, from the perspective of Islamic family law, the Baolek tradition is recognized as an authentic 'urf (custom) that aligns with societal values. It promotes social harmony, strengthens family ties, and fosters mutual support, making it a beneficial custom that is well-accepted within the community